A visual interactive tolerance approach to sensitivity analysis in MOLP - Borges, Ana Rosa Pereira (2002)
http://www.sciencedirect.com/science/article/B6VCT-447DBMN-2/1/630bdb10d9f6ed6a3b1fd3e26ffae06c